Colorimetric recognition of lanthanide ions with a complexometric indicator array. Issue 14 (17th June 2021) - Zhang, Tiantian; Zhuo, Xiuzhi; Shi, Guoyue; Zhang, Min
Abstract : A colorimetric sensor array based on complexometric indicators is proposed for pattern recognition of 14 lanthanide ions. Abstract : A colorimetric sensor array based on complexometric indicators is proposed for pattern recognition of lanthanide ions. The complexometric indicators have abundant functional groups and can act as a platform for chromogenic reaction with various metal ions, including lanthanide ions. The subtle difference of the lanthanide ions' structure results in the difference of absorbance response between lanthanide ions and two chromogenic indicators (Alizarin Red and Erichrome Black T) in Tris-HCl buffer with two different pHs ( i.e., pH 7.4 and pH 8.5, colorimetric sensor array). Fourteen lanthanide ions were distinguished well with the newly designed colorimetric sensor array. The sensor array has the potential to distinguish between different concentrations of lanthanide ions and their mixtures. Moreover, the results in actual samples indicate the future practical applications of this sensor array in environmental analysis.